Temperature‐Dependent Spin–Orbit Torques in Perpendicular Magnetic [Co/Ni]N/TbCo Composite Films. (4th April 2019) - Xue, Hongwei; Chen, Shaohai; Wu, Di; Zhu, Weihua; Zhang, Yuanyuan; Duan, Chungang; Chen, Jingsheng; Jin, Qingyuan; Zhang, Zongzhi
Abstract: The temperature ( T ) dependence of spin–orbit torque (SOT) efficiencies and magnetic properties are investigated in antiferromagnetically coupled Ta/Cu/[Co/Ni]N /TbCo perpendicular composite films. By changing the Co/Ni repetition number N, the magnetization compensation temperature T M can be widely modulated, decreasing from 295 K for N = 0 to below 10 K for N = 2. From temperature‐dependent harmonic Hall measurements, it is shown that damping–like SOT field per current density χDL = H DL / J ac varies in a similar way to the net saturation magnetization M S and reaches a maximum at T = T M, whereas field‐like H FL /J ac is nearly independent with T . The observed slight deviation between χDL and 1/MS versus T curves at reduced temperatures is attributed to the increased spin Hall angle and interfacial spin transparency. It is found that the SOT efficiency ξ varies from −0.04 to −0.06 and even to −0.13 for N = 0, 1 and 2, respectively, suggesting ξ is intensively dependent on the details of the Ta/ferromagnet (FM) interface and the FM layer material. These results provide more insight into the SOT effects for exchange‐coupled perpendicular composite structures, which are valuable for developing high‐performance SOT devices. Abstract : A comprehensive investigation into temperature‐dependent magnetic and transport properties is performed in a perpendicularly magnetized Ta/Cu/[Co/Ni] N = 0, 1, 2 /TbCo system. The magnetization compensation temperature T M and spin–orbit torque efficiency ξ can be modulated by changing the Co/Ni repetition number N . It is believed that the Ta/ferromagnet (FM) interface details and FM layer material play a major role in the variation of ξ.